Supporting Caregivers of Patients with Childhood Malignancies - Tsitsi, Theologia; Michail, Koralia (My University, 2023)
Parenting a child with malignancy can be demanding. The shift from parenting to caregiving for a child with cancer comes with the emotional, financial, and social burden that accumulates. Caregivers can often be diagnosed with Posttraumatic Stress Syndrome -PTSS, depression, and anxiety. The needs of caregivers of children with malignancies differ according to the diagnosis, the disease stage, the family structure, and their cultural and religious beliefs. Supporting these needs is essential for ensuring the continuity of the child’s therapy. Support methods have been described extensively in the literature. Healthcare providers in the field of pediatric cancer should be able to recognize the needs of caregivers and provide or guide them toward adequate and proper support. Supporting caregivers' needs has an immediate impact on the child’s treatment trajectory and outcome.
Keywords: childhood malignancies; caregivers